Characterisation and properties of calcium phosphate bioceramic derived from animal bones / Loo Zi Zhen - Loo, Zi Zhen (2018)
Hydroxyapatite is being considered for applications in biomedical mainly due to its calcium to phosphorus ratio being similar to that of hard tissues, possessed excellent biocompatibility and exhibited superior osteoconduction characteristics. The synthesis of hydroxyapatite by using synthetic chemicals as the starting calcium precursors has been widely reported however the development of hydroxyapatite from using natural calcium source such as from bovine bones, eggshells, oyster shells, fish bones and corals are not systematically investigated as a potential resources for the production of high quality hydroxyapatite. In this work, the viability of preparing hydroxyapatite using natural available animal bones through a thermal decomposition method applied to bovine bone, caprine bone and galline bone have been investigated. The bone samples were sourced locally, cleaned to remove fats and proteins followed by calcination in an air atmosphere at different temperatures ranging from 600°C to 1000°C. The calcined powders were prepared and characterized to determine the phases present using X-ray diffraction and FTIR. The results revealed that the thermal stability of the HA matrix was not disrupted, particularly for the bovine bone and that all of the sintered bodies exhibited phase pure HA. This was not the case for the caprine and galline bones where a small amount of bioresorbable tri-calcium phosphate phase was observed after the calcination process. Nevertheless, bovine and caprine bone heat treated at 750°C and galline bone at 600°C were identified as the optimum calcination temperatures. Therefore heat treated powder at optimum temperatures was used to produce green bodies for the sintering process. The bulk density and mechanical properties of sintered samples were also measured.